PEDAGOGICAL TECHNOLOGIES BASED ON EFFECTIVE ORGANIZATION AND MANAGEMENT OF EDUCATIONAL PROCESS (British Journal of Global Ecology and Sustainable Development, 2023)
In order to provide quality education to the young generation, educators in kindergartens and teachers in schools need to work tirelessly on themselves. For this, the manager of the educational organization is required to establish proper management. The innovative activity of the school director consists of organizing the activity of the educational institution in accordance with the changes in the external environment, planning and forming the regular development of the educational institution based on coordination, and includes three main components: creative, analytical and research. The innovative management system of the head of the educational institution is considered creative according to its particular characteristics.In this article, the author tried to show that the improvement of management, its development and the use of various non-traditional technologies in management serve as the basis of quality education.